2014
DOI: 10.1093/pcp/pcu209
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Characteristics and Differences in Arabidopsis Stigmatic Papilla Cells Pre- and Post-Pollination

Abstract: Pollination is an important early step in sexual plant reproduction. In Arabidopsis thaliana, sequential pollination events, from pollen adhesion onto the stigma surface to pollen tube germination and elongation, occur on the stigmatic papilla cells. Following successful completion of these events, the pollen tube penetrates the stigma and finally fertilizes a female gametophyte. The pollination events are thought to be initiated and regulated by interactions between papilla cells and pollen. Here, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Thus, genes related to tubulin binding might regulate self-pollen rejection by affecting the stability of MT network. In addition, compared to previous studies, a quantity of DEGs were also represented here, such as genes related to jasmonic acid production and plant-type cell wall metabolism were up-regulated at late stage in UP vs. PC samples, which is consistent with results reported by Swanson et al (2005) and Matsuda et al (2014). Most genes involved in stress response or defense response were up-regulated in both incompatible and compatible reactions at late-time points (20 and 30 min after pollination), while the unique proteins in the same GO terms were found to be down-regulated in incompatible pollination previously (Samuel et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, genes related to tubulin binding might regulate self-pollen rejection by affecting the stability of MT network. In addition, compared to previous studies, a quantity of DEGs were also represented here, such as genes related to jasmonic acid production and plant-type cell wall metabolism were up-regulated at late stage in UP vs. PC samples, which is consistent with results reported by Swanson et al (2005) and Matsuda et al (2014). Most genes involved in stress response or defense response were up-regulated in both incompatible and compatible reactions at late-time points (20 and 30 min after pollination), while the unique proteins in the same GO terms were found to be down-regulated in incompatible pollination previously (Samuel et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…A total of 37 metabolic pathways were identified. Starch and sucrose metabolism is one of the three most over-represented metabolic pathways, which has been reported by Matsuda et al (2014). Biosynthesis of antibiotics, and cysteine and methionine metabolism pathways are first annotated in this study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Considering AtPIP1;4 was found to be up-regulated in stigmas upon compatible pollination (Matsuda et al, 2015) and has a role in H 2 O 2 transport for signal transduction in immunity pathways (Tian et al, 2016), we could speculate a role of this AQP in ROS signaling during pollination.…”
Section: Seeking Their Physiological Rolementioning
confidence: 98%
“…Comparative analysis of pistil transcriptomes revealed the expression of PIP1 and PIP2 in species with dry and semi-dry stigmas ( Oryza sativa, Crocus sativus, Arabidopsis thaliana , and S. squalidus ), but not with wet stigmas ( Nicotiana tabacum ) (Allen et al, 2010). Recently, stigmatic papilla cells transcriptome analysis in A. thaliana ecotype Oldenburg (Old-1), which still retains the female SI function, showed that PIP1;4 is up-regulated in compatible pollinations (using wild-type Old-1 pollen), whereas PIP2;1 and PIP2;7 are down-regulated in incompatible pollinations (using transgenic self-incompatible Old-1 pollen) (Matsuda et al, 2015). These studies support the hypothesis of pistil AQP s potentially regulating pollen hydration in dry stigmas but not in wet stigmas, since the presence of the stigmatic exudate obviates the control of water flow to pollen grains.…”
Section: Pollen Aquaporins: Only Four Aqp Genes Are Pollen-specificmentioning
confidence: 99%